2020
DOI: 10.3390/rs13010049
|View full text |Cite
|
Sign up to set email alerts
|

Salt Marsh Elevation Limit Determined after Subsidence from Hydrologic Change and Hydrocarbon Extraction

Abstract: Levee construction aboveground and hydrocarbon removal from belowground in coastal wetlands can create hydrologic changes that increase plant stress through flooding. But the significance of the subsidence they cause individually or in combination is contested. This study untangled them to demonstrate elevational limits of salt marshes by studying dredged and natural waterways in two salt marshes in Louisiana, USA. The areas had a homogenous plant cover before drilling for oil and gas extraction peaked in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…Migratory fish do not have access to the canal, but grassbeds may be more abundant there that birds may be attracted to Neill and Turner, 1987a,b. A plug, however, blocks boat access which may help reduce erosion because of boat wakes at the canal's entrance (Turner and Mo, 2021).…”
Section: Restorationmentioning
confidence: 99%
See 1 more Smart Citation
“…Migratory fish do not have access to the canal, but grassbeds may be more abundant there that birds may be attracted to Neill and Turner, 1987a,b. A plug, however, blocks boat access which may help reduce erosion because of boat wakes at the canal's entrance (Turner and Mo, 2021).…”
Section: Restorationmentioning
confidence: 99%
“…Restoring wetlands is focused on mitigating these blockages to the water flow above-and belowground because they create both longer flooding periods and longer drying cycles; as a result a dose-response relationship between canals and land losses occurs over time and space (Turner and McClenachan, 2018). The volume of oil and gas extracted thousands of meters beneath the canal can be high enough to cause soil subsidence at the surface that results in unhealthy flooding of emergent plants (Stagg et al, 2019;Turner and Mo, 2021). A logical case can be made, based on these cause-andeffect relationships and others, that canals and their levees, and the fluid extraction made possible beneath them are a major cause of Louisiana's coastal wetlands from the 1930s to the present (Turner and McClenachan, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Subsidence in Louisiana’s wetlands is rapid at 9 ± 1 mm per year (Jankowski et al, 2017; Nienhuis et al, 2017), which is expected as a natural part of the delta lobe cycle (Yuill et al, 2009). However, continued hydrocarbon extraction, and the position of shipping canals in the marshes, has changed the hydrology of the modern delta, resulting in prolonged lower ground water level, which contributes to more rapid shallow subsidence than would be natural (Nienhuis et al, 2020; Turner and Mo, 2021).…”
Section: Future Of the Mississippi River And Its Deltamentioning
confidence: 99%
“…Nevertheless, some studies raise concerns that saltmarshes may experience habitat loss due to high rates of sea level rise (SLR) in combination with decreasing sediment availability [(for example due to damming of rivers; see Grill et al (2019)], so that vertical sediment accretion may not be sufficient to keep pace with global SLR (Reed, 1995;Weston, 2014). In some areas, subsidence caused by water, oil, or gas extraction adds to drowning of the saltmarsh (Turner and Mo, 2020). On the other hand, Kirwan et al (2016) showed in their meta-analysis that saltmarshes are more resilient to SLR than widely assumed.…”
Section: Introductionmentioning
confidence: 99%